Causes of Rational Eating Disorders in Children and Adolescents (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
An eating disorder is a serious mental illness.Changes in food and eating behaviours, and feeling unhappy with body shape and size are common risk factors and potential signs of the onset of an eating disorder Eating disorders are increasing in children under the age of 12.Parents, teachers and other adults can help to prevent eating disorders through role modelling a healthy relationship with food, exercise and their body.